GANGGUAN DEPRESIF ORGANIK (F06.32) PADA PASIEN DENGAN INFEKSI HIV - Alexandra Adeline (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Organic depressive disorder is a mood disorder that arises as a direct consequence of medical conditions, including advanced-stage Human Immunodeficiency Virus (HIV) infection, which may lead to neuropsychiatric complications and significantly affect patients’ psychosocial functioning and quality of life. This article aims to describe the clinical characteristics, diagnostic process, and management of organic depressive disorder in a patient with stage IV HIV. This study employed a case report design using data obtained from autoanamnesis, heteroanamnesis, mental status examination, physical examination, and relevant supporting investigations. The patient was a 26-year-old male presenting with persistent sadness, hopelessness, sleep disturbance, and loss of interest in daily activities. Clinical evaluation indicated depressive symptoms associated with the underlying medical condition without any prior history of mood disorder, leading to a diagnosis of organic depressive disorder (F06.32). Management was carried out comprehensively through a Consultation and Liaison Psychiatry approach, including antidepressant pharmacotherapy, supportive psychotherapy, and psychoeducation for both the patient and family. The findings showed an improvement in the patient’s emotional condition and psychosocial functioning following the integrated intervention. This case highlights the importance of early detection of psychiatric disorders in patients with advanced HIV and the need for a multidisciplinary approach to improve clinical outcomes and quality of life. ABSTRAK Gangguan depresif organik merupakan gangguan mood yang muncul sebagai akibat langsung dari kondisi medis tertentu, salah satunya infeksi Human Immunodeficiency Virus (HIV) stadium lanjut yang dapat menimbulkan komplikasi neuropsikiatri dan berdampak pada fungsi psikososial serta kualitas hidup pasien. Artikel ini bertujuan mendeskripsikan karakteristik klinis, proses diagnostik, dan penatalaksanaan gangguan depresif organik pada pasien HIV stadium IV. Penelitian ini menggunakan metode laporan kasus dengan data yang diperoleh melalui autoanamnesis, heteroanamnesis, pemeriksaan status mental, pemeriksaan fisik, serta pemeriksaan penunjang yang relevan. Pasien adalah laki-laki berusia 26 tahun dengan keluhan perasaan sedih berkepanjangan, putus asa, gangguan tidur, dan penurunan minat aktivitas. Evaluasi klinis menunjukkan gejala depresif yang berkaitan dengan kondisi medis yang mendasari tanpa riwayat gangguan mood sebelumnya, sehingga ditegakkan diagnosis gangguan depresif organik (F06.32). Penatalaksanaan dilakukan secara komprehensif melalui pendekatan Consultation and Liaison Psychiatry yang meliputi farmakoterapi antidepresan, psikoterapi suportif, dan psikoedukasi kepada pasien serta keluarga. Hasil menunjukkan adanya perbaikan kondisi emosional dan fungsi psikososial pasien setelah intervensi terpadu diberikan. Laporan ini menegaskan pentingnya deteksi dini gangguan psikiatri pada pasien HIV stadium lanjut serta perlunya pendekatan multidisiplin untuk meningkatkan luaran klinis dan kualitas hidup pasien.